Market Sensing Capability and Catering Product Innovation: The Role of Knowledge Creation and Entrepreneurship Orientation - Salma Abdullah; Ampauleng Ampauleng (Universitas Hayam Wuruk Perbanas, 2023)
Catering industry stakeholders must possess effective market sensing capabilities to thrive in the competitive market landscape. This study aims to scrutinize how these capabilities impact the innovation of catering products. Additionally, it delves into the pivotal roles played by the knowledge creation process as a mediating factor and entrepreneurial orientation as a moderating factor. The research model is meticulously crafted to mirror the real-world dynamics experienced in the catering sector. For this study, the focal point of analysis is the managers and employees (specifically chefs) of 27 small and medium-sized catering enterprises in Makassar City, known for their proficiency in providing pertinent insights into the research questions. The data is subjected to rigorous examination through a structural equation model, utilizing WarpPLS 7.0 software. The findings unveil that while market sensing capability does not wield a significant direct impact on product innovation, it does exert a positive and notable direct influence on the knowledge creation process. Moreover, the knowledge creation process emerges as a positive and substantial driver of product innovation. The relationship between market sensing capability and product innovation is further strengthened by the intermediary role of the knowledge creation process. This dynamic is further refined by the moderating influence of entrepreneurial orientation